Optimizing Nutrient Utilization and Microbial Protein Synthesis in Ruminants: Strategies for Enhanced Feed Efficiency and Sustainable Productivity - Shilpi Islam; Md. Emran Hossain (International Journal of Nutritions, 2026)
This review investigates strategies to optimize nutrient utilization and microbial protein synthesis in ruminants, aiming to improve feed efficiency and enhance overall livestock productivity sustainably. It focuses on key aspects of feed formulation, including balancing non-structural carbohydrates with protein sources, incorporating bypass proteins, and selecting high-quality forages that improve fiber digestibility. The review examines various feed processing techniques such as steam-flaking, pelleting, and ammonia treatment, which enhance nutrient bioavailability and microbial fermentation. Rumen modulation strategies, including the supplementation of buffers, ionophores, essential oils, and probiotics, are evaluated for their role in optimizing microbial activity and protein degradation. Additionally, the review highlights effective feed management practices, such as consistent feed mixing, maintaining optimal water intake, and preventing abrupt dietary changes to support rumen health and performance. Environmental and genetic approaches, such as breeding for improved feed conversion efficiency and developing climate-resilient feed crops, are also explored to address challenges related to feed availability and environmental stressors. The integration of precision feeding systems and real-time monitoring technologies is considered to further optimize nutrient delivery. By synthesizing these strategies, the review aims to provide actionable insights to enhance ruminant feed efficiency, reduce environmental impact, and promote sustainable livestock production.
Keywords: Feed formulation; Precision feeding; feed processing; microbial protein synthesis; rumen modulation; sustainable productivity